Deep Mycosis in Central Java, Indonesia: Occupational Risk Factors and Diagnostic Challenges in a Single Center Dr. Moewardi General Hospital - Nurrachmat Mulianto; Ivani (HM Publisher, 2025)
Background: Deep mycosis, a spectrum of invasive fungal infections affecting deeper tissues, poses significant diagnostic and therapeutic challenges, particularly in tropical regions like Central Java, Indonesia. This study aimed to investigate the epidemiological trends, occupational risk factors, and diagnostic challenges associated with deep mycosis in this region. Methods: A retrospective study was conducted at a single center, Dr. Moewardi General Hospital, in Central Java, Indonesia, analyzing medical records of patients diagnosed with deep mycosis between 2019 and 2024. Data on demographics, occupation, clinical presentation, diagnostic methods, and treatment outcomes were collected and analyzed. Results: A total of 12 cases of deep mycosis were identified. The majority of patients were male (75%) and engaged in agricultural activities (50%). Chromoblastomycosis (66.7%) and maduromycosis (25%) were the most common clinical diagnoses. Diagnostic delays were frequent (mean delay: 5.1 months), primarily due to non-specific clinical presentations and limited access to diagnostic facilities. Conclusion: Deep mycosis predominantly affects individuals involved in agriculture in Central Java, highlighting the need for enhanced awareness and preventive strategies among high-risk occupational groups. Improved diagnostic facilities and healthcare infrastructure are crucial for timely diagnosis and effective management of deep mycosis in resource-constrained settings.